INTELLIGENCE ANALYSIS OF THE ROLE OF THE FOREIGNER SUPERVISION UNIT OF THE TANGERANG POLICE INTELLIGENCE IN THE SUPERVISION OF FOREIGN WORKERS - Azhari, Apreza (International Review of Humanities Studies, 2023)
Human traffic flow in Indonesia is increasing due to various available facilities. As a result, more foreigners come to work in Indonesia. The presence of foreign workers then requires supervision so that they do not threaten the resilience of the Indonesian people. This paper aims to analyze the intelligence analysis process carried out by the Foreigner Supervision Unit of the Tangerang Police Satintelkam while supervising foreign workers at PT. CGC Indonesia. This research uses a qualitative descriptive method to collect data from a literature study. The analysis uses descriptive qualitative analysis and qualitative comparative analysis. The results show that foreign workers provide two main threats to regional resilience, especially in the economic sector, namely (1) the locals can lose their livelihoods because foreigners carry out too many economic activities; and (2) the locals can lose the opportunities to occupy important positions at work because the foreigners already fill the positions. This situation reflects the importance of intelligence monitoring by the Tangerang Police Intelligence unit. The monitoring is carried out with several institutions under the Foreigner Supervision Unit (Timpora). Supervision is conducted administratively through coordination, on-site supervision, open intelligence, and closed intelligence. Immigration intelligence plays a role in the early detection of foreigners' threats, including the disruption of territorial security caused by foreign workers with illegal permits.